Evaluation of pulmonary function data using computer time-sharing - Sullivan, S.F.; Patterson, R.W.; Papper, E.M. (Proceedings of the IEEE, 1969)
Evaluation of disturbances in lung function requires a variety of physiological measurements. Absolute values for such determinations are meaningless because the significance of the measured quantities varies with the age, sex, and body size of the subject. At present the norm which is compared with the measured value must be derived from tables or in some instances must be individually calculated. A computer program has been developed which evaluates the measured values of lung function by comparing them with accepted norms. The computer program is written in the BASIC programming language and minimal involvement by laboratory personnel is required. Stored in the computer program are matrices containing the regression coefficients used for the computation of the predicted values for each of the pulmonary function tests based upon the patient's sex, height, age, and weight. When the measured value falls outside of the 95 percent confidence limits, the measured value is flagged on a computer printout, immediately denoting those values which are abnormal. In approximately 5 minutes after the input of data, the printout evaluation is available for addition to the patient's record.